An Alternative Route to Complex Allenes or Cyclooctatrienes via a Suzuki Cyclocarbopalladation Cascade. Issue 4 (29th November 2021) - Flores, Océane; Locquet, Pierre; Suffert, Jean
Abstract: The 4‐ exo ‐dig cyclocarbopalladation of vinyl bromides substituted with a triple or double bond resulted in impressive cascade reactions leading to different compounds under Suzuki cross‐coupling conditions upon a slight modification of the starting material. When the starting compound carries a triple bond, a single cascade occurs providing a structure containing an allene, a tetrasubstituted cyclopropane, and a cyclobutene with complete stereoselectivity. When the related starting material possessing a double bond is reacted under the same conditions in the presence of various vinyl boronic esters or acids, an efficient 8π‐electrocyclization provides tricyclic systems comprised of a cyclobutene unit, as well as a cyclooctatriene. Five carbons of the latter can be selectively decorated with different substituents depending on the choice of the starting material and the boronic coupling partner. Abstract : The preparation of elaborate polycycles using the Suzuki cross‐coupling reaction has been developed. If compounds 1 a –c are substituted by a triple bond an unusual cascade reaction affords allene derivatives 3 stereoselectively, while the presence of a substituted double bond, when reacted with a boronic ester or acid on 4, furnishes polysubstituted cyclooctatrienes 22 in high yields.